When war played through : golf during World War II - Strege, John. (New York : Gotham Books, 2005)
How golf boosted moral in WWII, from which it began its climb to its tremendous popularity today. Autographed copy.
Golf on a day of infamy : the Pearl Harbor attack -- It's your duty to play more golf : the game's first response -- War comes to Augusta : the 1942 Masters and PGA Championship -- A medal for Hogan : the Hale America Open -- The grass is not greener : the clubs and the war -- Autumn leaves and a Spalding dot : shortages hit golf -- Hunkering down : an elite sport comes under attack -- Eisenhower and Jones : warriors -- A call to serve : the pros go to war -- Good enough to play with Snead and Nelson : Burke and Bourisseau -- Stalag golf : POWs play through -- D-Day : golf and Operation Overlord -- Soldiering on, hole by hole : golf keeps up the fight -- A game's resilience : golf rebounds -- Ben who? and Lord Byron : the greatest streak in golf history -- The greatest boom of all time : golf moves from the war zones to home -- Worthy champions: the Masters resumes.
Includes index.
Keywords: Golf and war -- United States -- History; World War, 1939-1945 -- Social aspects -- United States; United States -- Social life and customs -- 1918-1945.